PENGARUH MACAM MULSA DAN DOSIS PUPUK KANDANG SAPI TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KACANG TANAH (Arachis hypogaea L.) - Ambarsari, Widi Komala; Maryani, Yekti; Susilaningsih, Sri Endah Prasetyowati (Universitas Sarjanawiyata Tamansiswa, 2019)
This study aims to determine the effect of mulch type and cow manure dosage on the growth and yield of cultivated peanut plants. Experiments were carried out at the